Marketing Strategy that Helped Oziva: The Health and Wellness Brand - Paul, Swastika (International Journal of Engineering and Management Research, 2026)
Fast life and life choices has a huge impact on our lifestyles and health which mostly drain us physically or mentally. OZiva, a plant-based clean-label nutrition and wellness brand, has thus leverage this fast pace life and capitalizing on the situation came up with quick solutions to modern day problems which they promoted via social media , digital marketing and through paid collaboration . This paper examines the marketing strategies adopted by Oziva which helped them in brand positioning and attain customers to create the brand loyalty they have now while also increasing their sales revenue. The study is based on secondary data, case analysis, and observation of digital marketing practices. Findings suggest that OZiva’s strategies to position their brand according to their values through paid collaborations with trusted influencers have given them a safe viable place to influence the consumers and thus had adopted a customer centric approach.